2020
DOI: 10.3855/jidc.12091
|View full text |Cite
|
Sign up to set email alerts
|

Colonization by multidrug-resistant microorganisms of hospitalized newborns and their mothers in the neonatal unit context

Abstract: Introduction: The mother plays a fundamental role in the constitution and regulation of her child's healthy microbiota, however, preterm newborns are separated from their mothers soon after birth and transferred to Neonatal Intensive Care Units, being exposed the constant risk for the development of multidrug-resistant microorganisms’ infections. The aim of this study was to explore the multidrug-resistant microorganism colonization of hospitalized babies and their mothers in the neonatal unit context. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
1
11
3
Order By: Relevance
“…However, Smith et al (2010) reported an association between vaginal delivery and bloodstream infection with GNB [14]. In contrast to the results of other studies, we did not find any association of the maturity level of the newborns and the risk of acquiring MDR bacterial colonization or infection [3,20,[26][27][28]32]. Haase et al (2014) detected low gestational age and need for mechanical ventilation as risk factors for colonization with MDR bacteria [20], Sakai et al (2020) found an association with prematurity, extremely low birth weight, and non-exclusive breastfeeding [32].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, Smith et al (2010) reported an association between vaginal delivery and bloodstream infection with GNB [14]. In contrast to the results of other studies, we did not find any association of the maturity level of the newborns and the risk of acquiring MDR bacterial colonization or infection [3,20,[26][27][28]32]. Haase et al (2014) detected low gestational age and need for mechanical ventilation as risk factors for colonization with MDR bacteria [20], Sakai et al (2020) found an association with prematurity, extremely low birth weight, and non-exclusive breastfeeding [32].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the results of other studies, we did not find any association of the maturity level of the newborns and the risk of acquiring MDR bacterial colonization or infection [3,20,[26][27][28]32]. Haase et al (2014) detected low gestational age and need for mechanical ventilation as risk factors for colonization with MDR bacteria [20], Sakai et al (2020) found an association with prematurity, extremely low birth weight, and non-exclusive breastfeeding [32]. Auriti et al (2003) found a higher risk of contracting hospital acquired infections for infants with a very low birth weight, low gestational age and intravascular catheters [3].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The American Type Culture Collection (ATCC) strain E. coli 25922 was used as the control. Strains resistant to more than three antibiotics belonging to different categories were classified as multidrug-resistant (MDR) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…12 Studies highlighted that frequent and unselective usage of broad spectrum antibiotics without consideration of culture and Susceptibility reporting leads to the development of multidrug resistant microorganisms (MDRs). 13 These MDRs are frequently colonized through endogenous or exogenous sources on life saving instruments such as Mechanical Ventilators in ICUs. 14 Bacteriological examination of respiratory secretions offer helping hand to clinician in diagnosing VAP and also helps him to initiate early antibiotic regimen.…”
Section: Introductionmentioning
confidence: 99%